Myopericytoma involving the right renal pelvis and ureter: A case study - Liska Budding; Sarel F. Rothman; Jacqueline Goedhals (Elsevier, 2020)
Myopericytomas are benign tumours that usually affect the peripheries and are rarely found in the viscera. Only 10 cases of renal myopericytoma have been reported in the literature since 2010. In this case study, we discuss a 51-year-old African female patient who presented to the urology clinic with complaints of haematuria and flank pain. Investigations were conducted that revealed right-sided hydronephrosis with a solid mass originating from the renal collecting system and extending to the renal pelvis and ureter. A right nephrectomy and bladder cuff excision was conducted and the mass was completely excised. Microscopic examination of the tissue showed the presence of plump, spindle-shaped cells with oval nuclei and a concentric perivascular growth pattern. The lesion stained positive for markers of smooth muscle differentiation and a renal myopericytoma was diagnosed. The patient recovered well following surgery and had no further complaints on follow-up consultation. In addition to describing this case, we compared our case to those reported since 2010.